2016
DOI: 10.20533/iji.1742.4712.2016.0148
|View full text |Cite
|
Sign up to set email alerts
|

Using Adaptive Comparative Judgement to Assess Student Work in an MBA Course

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A number of CJ studies have further shown high interrater reliability scores among trained and untrained raters (Heldsinger & Humphrey, 2013; Jones & Alcock, 2014; Jones & Inglis, 2015; Jones, Swan, & Pollitt, 2015; McMahon & Jones, 2015; Metzgar, 2016). Pollitt (2012) indicated untrained raters competently assessed writing quality and achieved absolute reliability (an equivalent of Cronbach's α ) estimates of .96 of the objects rated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of CJ studies have further shown high interrater reliability scores among trained and untrained raters (Heldsinger & Humphrey, 2013; Jones & Alcock, 2014; Jones & Inglis, 2015; Jones, Swan, & Pollitt, 2015; McMahon & Jones, 2015; Metzgar, 2016). Pollitt (2012) indicated untrained raters competently assessed writing quality and achieved absolute reliability (an equivalent of Cronbach's α ) estimates of .96 of the objects rated.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have advocated for wider adoption of CJ based on its high reliability as measured in a range of assessment domains across a number of studies (Bramley, 2007;Jones & Inglis, 2015;Pollitt, 2012;Steedle & Ferrara;2016). None of these studies, however, examined CJ reliability when rating texts composed by English as a second language (ESL) writers, whose language skills and organizational patterns may make it difficult for raters to agree on relative essay quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Last, traditional assessments such as written exams and quizzes often test conceptual understanding and are simple to develop and implement. Compared to experiential learning-based assessments, less ambiguity and subjectivity are involved during evaluation and grading [ 39 ]. Some differences among them are related to frequency and content volume.…”
Section: Methodsmentioning
confidence: 99%
“…Given the impact of psychological safety in motivating individuals to seek out feedback, we contend that further research is needed as to the influence the strategies by which leaders or instructors implement peer review and feedback processes into the teams they oversee have on the construct. ACJ is one such strategy for peer review and feedback, and though it has only once been used in business education to assist in peer evaluation (Metzgar, 2016), how ACJ influences psychological safety within teams is greatly under-researched. Therefore, a particular interest for our study was the interaction and impact of peer review using ACJ on one's ability to take interpersonal risks.…”
Section: Psychological Safetymentioning
confidence: 99%